Characterization of an IgM-like immunoglobulin from silver catfish (Rhamdia quelen) serum and its use for the production of polyclonal antibodies and development of immunoassays - Kreutz,Luiz C. (2016)
Abstract: Knowledge on fish immunoglobulin (Ig) characteristics and the availability of monoclonal or polyclonal antibodies to fish Igs are essential to evaluate the humoral immune response and the Ig distribution on leukocyte cells. We demonstrated that silver catfish serum Ig is composed of one immunodominant H chain with approximately 75k Da and one L chain with approximately 28 kDa, similar to human IgM. Rabbit polyclonal antibodies to the catfish IgM-like Ig recognized both the H and L chain and were useful in developing an indirect ELISA to measure the production of antibodies in fish immunized with bovine serum albumin. Dot blot and western blot cross-reactivity studies indicated a wide degree of epitope sharing amongst Ig from several Siluriformes and Characiformes fish indigenous to Brazilian rivers. In these fish species, polyclonal antibodies reacted mostly with the H chain. The results presented here are central to the development of tools and strategies to investigate the antibody production to inoculated antigens and tissue distribution of Ig molecules in native fish species. Furthermore, because of the wide range of cross-reactivity, polyclonal antibodies to silver catfish IgM-like Ig might be used to develop immunoassays to measure the humoral immune response in other fish species.